A multi-disciplinary approach to identify spillover interfaces of bat coronaviruses to pig farms in Italy - Francesca Festa; Pamela Priori; Giulia Chiarello; Elisa Palumbo; Gianpiero Zamperin; Francesca Cosentino; Luigi Maiorano; Maria Luisa Menandro; Dino Scaravelli; Paola De Benedictis; Pierre Nouvellet; Stefania Leopardi (PLoS ONE, 2025)
Bats are recognized reservoirs of diverse coronaviruses (CoVs), but little is known about the pathways enabling their spillover into livestock. This study applied a multidisciplinary approach, combining bioacoustic surveys, landscape analysis and molecular virology, to assess the risk of CoV transmission from bats to pigs in intensive farming systems of Northern Italy. Between 2021 and 2022, we carried out bioacoustic monitoring in 14 pig farms to assess bat presence, diversity and behaviour. We also analysed landscape and farm-level variables to identify predictors of bat activity and richness. Additionally, we investigated CoV circulation in three populations of Pipistrellus kuhlii through active longitudinal surveillance, performing whole-genome sequencing on new and archival CoV strains detected in P. kuhlii and Hypsugo savii. Using these data, we explored the viral biodiversity potentially present at this interface via genetic and phylogenetic analyses. We identified eight bat species across farms, with P. kuhlii, P. pipistrellus and H. savii being the most widespread and active. Landscape and structural analysis revealed that farm features attracting insects were associated with higher bat activity, while the surrounding habitat showed little effect. Crucially, we found frequent absence of physical barriers preventing contact between bats or their droppings and pig enclosures, increasing exposure risks. Focusing on the most common bat species, we detected active CoV circulation in P. kuhlii, including colonies located near pig facilities. Two distinct CoV species were identified in P. kuhlii, suggesting potential for viral recombination. CoVs were detected throughout the active season, with amplification peaks in May and August. Phylogenetic analysis indicated that pigs could be exposed to at least eight bat CoV species in Italy. Notably, CoVs appeared to be shared between P. kuhlii and H. savii, further increasing recombination risks. Our study outlines a potential transmission route of bat CoVs to swine and highlights key risk factors, including farm structures, biosecurity gaps, bat species involved, viral diversity and seasonal patterns of virus circulation.